Children, kitchen, church: does ethnicity matter? - Anzelika Zaiceva; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Gender role attitudes are well-known determinants of female labor supply. This paper examines the strength of those attitudes using time diaries on childcare, food management and religious activities provided by the British Time Use Survey. Given the low labor force participation of females from ethnic minorities, the role of ethnicity in forming those attitudes and influencing time spent for traditional female activities is of particular interest. The paper finds that white females in the UK have a higher probability to participate in the labor force than non-white females. Non-white females spend more time for religious activities and, to some extent, for food management than white females, while there are no ethnic differences for time spent on childcare. The ethnicity effect is also heterogenous across different socio-economic groups. Hence, cultural differences across ethnicities are significant, and do affect work behavior.
Keywords: J22; J15; J16; 330; Time use; ethnic minorities; gender; UK.; Frauenerwerbstätigkeit; Arbeitsangebot; Frauen; Ethnische Gruppe; Zeitbudgetforschung; Migranten; Großbritannien